2020
DOI: 10.1002/cm.21596
|View full text |Cite
|
Sign up to set email alerts
|

Actin filaments modulate electrical activity of brain microtubule protein two‐dimensional sheets

Abstract: The cytoskeleton of eukaryotic cells contains networks of actin filaments and microtubules (MTs) that are jointly implicated in various cell functions, including cell division, morphogenesis, and migration. In neurons, this synergistic activity drives both the formation of axons during development and synaptic activity in mature neurons. Both actin filaments and MTs also are highly charged polyelectrolytes that generate and conduct electrical signals. However, no information is presently available on a potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 63 publications
3
11
0
Order By: Relevance
“…Although the oscillating behavior has been observed in other MT structures (10,11), the electrical behavior of isolated MTs was somewhat richer, and consistent with the presence of several fundamental frequencies that cancel out and disappear to offer more coherent behavior in brain MT sheets. MT electrical oscillations in the neuronal environment may provide a novel means for interactions between different cellular organelles and/or cytoskeletal structures as we recently observed in the context of interactions between MT sheets and actin filaments (16). Finally, the present study sheds new light into the structural/functional correlates of MT electrical oscillations (Fig.…”
Section: Resultssupporting
confidence: 76%
“…Although the oscillating behavior has been observed in other MT structures (10,11), the electrical behavior of isolated MTs was somewhat richer, and consistent with the presence of several fundamental frequencies that cancel out and disappear to offer more coherent behavior in brain MT sheets. MT electrical oscillations in the neuronal environment may provide a novel means for interactions between different cellular organelles and/or cytoskeletal structures as we recently observed in the context of interactions between MT sheets and actin filaments (16). Finally, the present study sheds new light into the structural/functional correlates of MT electrical oscillations (Fig.…”
Section: Resultssupporting
confidence: 76%
“…In both cases, the oscillatory behavior peaked at frequencies around 40 Hz and 90 Hz. The findings are in general agreement with the oscillatory behavior of mammalian brain MT sheets (Cantero et al, 2016 , 2020 ) and membrane-permeabilized murine hippocampal neurons (Cantero et al, 2018 ). A couple of differences are worth noting, however.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies from our laboratory showed that different mammalian brain MT structures including 2D-sheets and bundles generate strong electrical oscillations [22,23] that resemble those observed in isolated MTs [24]. This electrical behavior of MTs is mechanistically consistent with electrochemical transistors that support both amplification and self-sustained current-(and voltage-) oscillations [22,23,24,25,26]. From a structural viewpoint, the distinct electrical activity of the various brain MT structures [22,23] is linked to the particular ensemble of MT subunits.…”
Section: Introductionsupporting
confidence: 73%
“…Voltage-clamped bundles of brain MTs display electrical oscillations with a prominent fundamental frequency at ~39 Hz that progress through various periodic regimes. Membrane-permeabilized neurites of cultured mouse hippocampal neurons also generate electrical oscillations conducted along their length [23,25,26]. Thus, the electrical activity of MTs remains evolutionarily conserved, despite functional heterogeneity of the different tubulin genes, encoding isotypes in the various tissues, and diverse posttranslational modifications of the tubulins [46,47,48].…”
Section: Discussionmentioning
confidence: 99%